The Analysis of Connotative Meaning in Taylor Swift’s Song Lyrics - , Paulina Bura Kaka; Emi Mura Isu; I Putu Eka Suardana (Universitas Bali Dwipa, 2025)
This research investigates the connotative meanings found within selected Taylor Swift song lyrics to explore the emotional, symbolic, and cultural dimensions that extend beyond their literal meanings. The study focused on ten songs from the years 2010 to 2022, purposefully chosen from albums like Red, 1989, Reputation, and Folklore due to their rich thematic content and lyrical complexity. As the data comprised only textual lyrics, no human participants were involved. Employing a qualitative descriptive design, the researcher transcribed the lyrics and conducted an in-depth analysis based on Leech’s (1974) theory of connotative meaning. This involved examining metaphorical phrases, emotionally expressive vocabulary, and culturally significant references. The analysis revealed that Swift consistently incorporates connotative language to express intricate emotions such as longing, heartbreak, empowerment, and nostalgia. Her lyrics also present ideas related to identity, personal development, romantic dynamics, and societal issues, deepening the interpretive experience for listeners. Ultimately, the study highlights how Swift’s strategic use of connotation enhances the emotional resonance and narrative strength of her music, offering meaningful insights into the interplay between language and meaning in popular song lyrics.